Neuropsychological aspects of self-image in social media use - Krause, Robert; Krause, Martina (Frontiers in Psychology, 2025)
This research aimed to investigate the neuropsychological aspects of social media use on self-image among primary and secondary school girls. The study specifically focused on self-concept and body satisfaction. A total of 189 girls (95 primary school, 94 secondary school) between the ages of 10 and 19 (M = 14.94; SD = 2.57) participated. Each student completed the Self Perception Profile for Adolescents, the Body Esteem Scale, and a Social Media Inventory to measure their self-concept, body satisfaction, and social media usage habits, respectively. Out of all participants, 87.30% reported using Instagram, 73.54% used TikTok, 50.26% used Facebook, 14.29% used Twitter, and 55.61% used other platforms. On average, participants spent 239.73 min (nearly 4 h) on social media daily. A significant negative correlation was found between time spent on social media and age. A significant difference (t = 3.14; p = 0.002; 95% CI [35.96, 161.61]) was observed in social media usage between age groups, with primary school girls (M = 343.11; SD = 267.07) spending more time on these platforms than secondary school girls (M = 243.83; SD = 150.77). The study’s key finding was that social media behaviors (such as sharing photos and liking posts) did not show a statistically significant correlation with self-concept or body satisfaction. The study suggests that while social media use is extensive, specific behaviors on these platforms do not appear to be significant predictors of overall self-image and body satisfaction. This outcome carries a positive neuropsychological implication, indicating that the self-perception of girls in this age group may be more resilient to the direct influence of their social media actions than previously thought.